Efeito do reisolamento de fragmentos florestais sobre a dinâmica temporal de assembleias de peixes de Igarapés na Amazônia Central Brasileira - Gualberto, Claudia Gemaque (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Both deforestation and forest fragmentation are environmental disruption caused numerous consequences already registered for plants and terrestrial animal. However, the effects of these phenomena in aquatic systems and specifically on fish assemblages are scarcely known. The Biological Dynamics of Forest Fragments Project (PDBFF) has been studying the effects of forest fragmentation for more than three decades. For this isolated forest fragments experimentally must be reisolated periodically, and these predictable environmental disturbance events and controlled is the key to this work aimed to evaluate the re-isolation of the effects of forest fragments on the structure and composition of fish assemblages in streams of land in the Brazilian Central Amazon. We seek specifically: i) evaluate the re-isolation of the effects of forest fragments on the environmental characteristics of streams; ii) to evaluate the structure of stream fish assemblages in different environmental matrices before and after re-isolation and iii) To assess the ecological stability of stream fish populations subject to re-isolation. Samples were collected in streams four environments (continuous forest, mature secondary, forest fragment and coops) before and after the re-isolation of forest fragments (short term - a month and medium term - six months). The re-isolation of forest fragments affected the environmental characteristics of the streams, however, the structure of fish assemblages (richness, diversity and abundance) did not differ temporally and spatially. The results suggest that fish assemblages can partly withstand to the environmental disturbances resulting from the re-isolation, without departing from an equilibrium situation (resilience). However, we cannot discard the hypothesis that changes in fish assemblages may occur on a larger time scale, compatible with the generational time of stream fishes.